Cultural Elemens in the Texts of Sanja Pilić - Dragun, Dragica (Revija za elementarno izobraževanje, 2011)
The paper discusses some cultural views of the literary works of Sanja Pilić. Her methodological approach is based on the Raymond Williams’ three-part typology of culture: ideal, documentary and social. Guided by Williams’ classification of culture, the paper attempts to investigate how specific characteristics of each particular type are reflected in Sanja Pilić’s texts for children and youth.
Keywords: ideal, documentary and social culture; texts by Sanja Pilić